LC–MS/MS characterization of the urinary excretion profile of the mycotoxin deoxynivalenol in human and rat - Lattanzio, Veronica M.T.; Solfrizzo, Michele; De Girolamo, Annalisa; Chulze, Sofía N.; Torres, Adriana M.; Visconti, Angelo (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
The understanding of mycotoxins transfer to biological fluids is challenged by the difficulties in performing and replicating in vivo experiments as well as the lack of suitable methods of analysis to detect simultaneously a range of chemically different metabolites at trace levels. LC–MS/MS has been used herein to study the urinary excretion profile of the mycotoxin deoxynivalenol in human and Wistar rat. Deoxynivalenol and deoxynivalenol glucuronide were found in both human and rat urines, whereas de-epoxydeoxynivalenol and its glucuronide conjugate were only detected in rat urine. The presence of two deoxynivalenol glucuronide isomers in Wistar rat urine has been shown for the first time. Structure confirmation of the detected metabolites was provided by the analysis of fragmentation patterns. A solid phase extraction clean up procedure allowing recoveries in the range 72–102% for deoxynivalenol, de-epoxydeoxynivalenol, and their glucuronide conjugates was optimized. A multiple reaction monitoring method for the simultaneous determination of all investigated metabolites was elaborated allowing the direct detection of deoxynivalenol metabolites without the hydrolysis step. Deoxynivalenol urinary levels in the range 0.003–0.008 μg/ml were detected in healthy human subjects, whereas deoxynivalenol and de-epoxynivalenol levels between 1.9–4.9 μg/ml and 1.6–5.9 μg/ml, respectively were found in administered rat urine. These findings emphasize the relevance of the highly selective and sensitive LC–MS/MS technique for the direct detection and characterization of deoxynivalenol metabolites in complex biological matrices.